Teacher perspectives about English language teaching reforms in Vietnamese high schools - Thinh Van Le; Tien Minh Mai; Tran Le Nghi Tran; Luan Thanh Nguyen (Ho Chi Minh City Open University Journal of Science - Social Sciences)
In Vietnam, the Ministry of Education and Training (MOET) issues uniform curricula and textbooks, sets goals, and implements assessments nationwide for high school schools. This means every Vietnamese public high school has to use the prescribed textbooks to teach the same content following a page-by-page schedule throughout the school year, undergo identical assessment tasks, and try to maintain similar outcomes regardless of geographical or socio-economical differences. In such a system, classroom teacher’s voices are usually under-sounded and little research has been conducted on teachers’ perspectives regarding these crucial components of their profession. This study presents how high school EFL teachers perceive and cope with the top-down system in terms of objectives, curriculum, methodology, assessment and outcomes in Vietnam. Data were collected from 163 teachers using an online survey on their attitudes towards the objectives, curriculum, methodology, assessment, and outcomes as determined by MOET. The results showed a discrepancy in the curricula and assessment. While the curricula emphasized communicative competence, the assessment heavily focused on forms. As a result, although some teachers tried to diversify their teaching method, they eventually focused on grammar, reading comprehension and vocabulary for students to achieve satisfactory results in the national examination.